2010
DOI: 10.2478/v10011-010-0003-1
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Profiles in Nasal Fluid in Patients with Nasal Polyps: A Flow Cytometric Study

Abstract: Cytokine Profiles in Nasal Fluid in Patients with Nasal Polyps: A Flow Cytometric StudyBiological markers in nasal fluid provide valuable information on nasal pathophysiology. The aims of this study were to compare the cytokine profiles of nasal fluid in subjects with nasal polyps (NP) and co-morbid asthma and NP patients without asthma and to determine the role of these cytokines in the development of NP. Thirty patients with NP (15 asthmatic and 15 non asthmatic) were included in this prospective study. Nasa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 20 publications
(32 reference statements)
1
7
0
4
Order By: Relevance
“…IL-17 in the sputum, bronchoalveolar lavage fluid and serum has been found to markedly increase in asthma patients, and the extent of increase of the IL-17 level is related to the airway hyperrespon siveness and the degree of inflammation (13). Klemens et al (14) reported that IL-17 was detectable in the excretions of viral rhinitis patients and AR patients, but the IL-17 level in the viral rhinitis was dramatically higher than that in the AR patients. In addition, Ciprandi et al (15) found, in the pollen season, the serum level of IL-17 was closely relevant with the severity of clinical manifestations in patients with pollen induced AR.…”
Section: Discussionmentioning
confidence: 99%
“…IL-17 in the sputum, bronchoalveolar lavage fluid and serum has been found to markedly increase in asthma patients, and the extent of increase of the IL-17 level is related to the airway hyperrespon siveness and the degree of inflammation (13). Klemens et al (14) reported that IL-17 was detectable in the excretions of viral rhinitis patients and AR patients, but the IL-17 level in the viral rhinitis was dramatically higher than that in the AR patients. In addition, Ciprandi et al (15) found, in the pollen season, the serum level of IL-17 was closely relevant with the severity of clinical manifestations in patients with pollen induced AR.…”
Section: Discussionmentioning
confidence: 99%
“…Drveni štapić sa vatom na vrhu (deo sa vatom je dužine oko 10 mm, a širine oko 4 mm), tokom prednje rinoskopije postavlja se što bliže ili se drži u srednjem nosnom hodniku tokom 60 sekundi, koliko je potrebno da se komadić vate natopi nosnim sekretom (slika 2). Zatim se deo štapića sa vatom na vrhu odlomi i ubaci u ependorf epruvetu u kojoj se nalazi transfer-medijum (18)(19)(20)(21)(22)(23).…”
Section: ) Apsorpcione Tehnikeunclassified
“…Pošto se uzme uzorak nosnog sekreta, on se unosi u ependorf epruvetu u kojoj se nalazi 1 ml "transfer medijuma" (18)(19)(20)(21)(22)(23). To je fosfatno puferisani fiziološki rastvor sa 50 μg/ml gentamicina, 340 μg/ml penicilina G i 500 μg/ml fungizona, koji služe kao konzervansi i sprečavaju razmnožavanja bakterijskih i gljivičnih mikroorganizama u uzorku (18)(19)(20)(21)(22)(23). U "transfer medijumu" uzorak stoji minimalno 30 minuta, koliko je potrebno za difuziju citokina/hemokina iz uzorka sekreta, koji je hiperosmolalan u "transfer medijum", koji je hipoosmolalan.…”
Section: Merenje Protočnom Citometrijomunclassified
“…Nasal fluid samples were collected from nasal cavities of all 40 subjects (22 patients with nasal polyposis, and 18 patients with nasal polyposis and allergic rhinitis) before and within the seven days after the CAM treatment using modified absorption technique by placing cottonwool sticks (length 10 millimetres, diameter 4 millimetres; Institute of Virology, Vaccines and Sera, "Torlak", Belgrade, Serbia), into the nasal cavity posterior to the mucocutaneous junction for 60 seconds, as previously described 9,10 . All samples were placed in a 2 ml Eppendorf tube containing 1 ml of transfer medium (phosphatebuffered saline with gentamycin 50 μg/ml, penicillin G 340 U/ml, fungizone 500 μg/ml) for 30 min to allow diffusion of cytokines into the medium and then stored at 4 °C for a maximum of 2 h until processed.…”
Section: Sampling Of Nasal Fluid and Cytokine Determinationmentioning
confidence: 99%